Relationships of Sources of Meaning and Resilience With Meaningfulness and Satisfaction With Life: A Population-Based Study of Norwegians in Late Adulthood - Sørensen, Torgeir; Hestad, Knut; Grov, Ellen Karine (Frontiers in Psychology, 2021)
Health-promoting initiatives incorporating meaning-making to enhance the well-being of people in late adulthood are important, particularly as the number of elderly people is increasing. Resilience and sources of meaning are assumed to be related to individuals’ experience of meaningfulness and satisfaction with life. However, few studies have investigated these relations among people in late adulthood. In the present exploratory study we asked the following questions: What are the differences regarding scores on sources of meaning, resilience, meaningfulness, and satisfaction between people in late adulthood (≥ 65) and other adults (18–64)? What is the association between sources of meaning and meaningfulness, and resilience and meaningfulness? What is the association between sources of meaning and satisfaction with life, and resilience and satisfaction with life? A cross-sectional design was used. A population-based sample of 925 participants (aged 18–91 years) was recruited from the National Population Register in Norway. Of these, 219 participants were 65 years old and older. Independent-samples t-tests, chi-square tests, and linear regressions adjusted for demographics, anxiety, and depression were performed utilizing standardized questionnaires. It was found that people in late adulthood (≥ 65 years) scored significantly higher on meaningfulness compared to younger adults (18–64). Of the sources of meaning, vertical self-transcendence, including explicit religiosity and spirituality, had the strongest relation to meaningfulness for people in late adulthood, after adjusting for demographics, anxiety, and depression. For the same group, accomplishment, including generativity and unselfish engagement with the surroundings and future generations, also stood out as a prominent sources of meaning when related to meaningfulness. No sources of meaning were associated with satisfaction with life in the older group. Resilience was neither associated with meaningfulness nor with satisfaction with life among people in late adulthood. However, resilience was positively associated with both meaningfulness and satisfaction with life in the 18–64 age group. Longitudinal research and interventional studies are needed to confirm whether the designated sources contribute to meaningfulness in a Norwegian context. The implications of the findings are discussed.